Differential inflammasome activation predisposes to acute-on-chronic liver failure in human and experimental cirrhosis with and without previous decompensation. Issue 2 (2nd April 2020) - Monteiro, Sofia; Grandt, Josephine; Uschner, Frank Erhard; Kimer, Nina; Madsen, Jan Lysgård; Schierwagen, Robert; Klein, Sabine; Welsch, Christoph; Schäfer, Liliana; Jansen, Christian; Claria, Joan; Alcaraz-Quiles, José; et al.
Abstract : Objective: Systemic inflammation predisposes acutely decompensated (AD) cirrhosis to the development of acute-on-chronic liver failure (ACLF). Supportive treatment can improve AD patients, becoming recompensated. Little is known about the outcome of patients recompensated after AD. We hypothesise that different inflammasome activation is involved in ACLF development in compensated and recompensated patients. Design: 249 patients with cirrhosis, divided into compensated and recompensated (previous AD), were followed prospectively for fatal ACLF development. Two external cohorts (n=327) (recompensation, AD and ACLF) were included. Inflammasome-driving interleukins (ILs), IL-1α (caspase-4/11-dependent) and IL-1β (caspase-1-dependent), were measured. In rats, bile duct ligation-induced cirrhosis and lipopolysaccharide exposition were used to induce AD and subsequent recompensation. IL-1α and IL-1β levels and upstream/downstream gene expression were measured. Results: Patients developing ACLF showed higher baseline levels of ILs. Recompensated patients and patients with detectable ILs had higher rates of ACLF development than compensated patients. Baseline CLIF-C (European Foundation for the study of chronic liver failure consortium) AD, albumin and IL-1α were independent predictors of ACLF development in compensated and CLIF-C AD and IL-1β in recompensated patients. Compensated rats showed higher IL-1α gene expression and recompensated rats higher IL-1β levels with higher hepatic gene expression. Higher IL-1β detection rates in recompensated patients developing ACLF and higher IL-1α and IL-1β detection rates in patients with ACLF were confirmed in the two external cohorts. Conclusion: Previous AD is an important risk factor for fatal ACLF development and possibly linked with inflammasome activation. Animal models confirmed the results showing a link between ACLF development and IL-1α in compensated cirrhosis and IL-1β in recompensated cirrhosis.